Stock Price Reactions on NASDAQ Stock Exchange for Special Dividend Announcements - Seyedimany, Arian (Ital Publication, 2019)
Announcing dividend pay-out policy by a company will signals market firm’s future prospects and changes its stock prices according to dividend signalling theory. By analysis the effect of special dividend announcements for 5 companies listed in NASDAQ for the period of 2014-2018, this study investigates the stock price reactions to special dividend announcement for 40 days around the event and challenges dividend signalling theory. The empirical results calculated both in discrete and logarithmic forms. Only few disordered significant abnormal returns and average abnormal returns occurred according to the t-test. The results show that shareholders do not gain value from announcement of special dividend in NASDAQ stock exchange market. That Results indicated from adjusted market model in this research do not support dividend-signalling theory Hence do not confirm that the announcement of dividend has significant effect on price of shares. In general the results consistent with the Miller and Modigliani (1961) dividend irrelevance hypothesis.